2018
DOI: 10.1186/s13256-018-1692-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-Partum Thrombotic Thrombocytopenic Purpura (TTP) in a Patient with known Idiopathic (Immune) Thrombocytopenic Purpura: a case report and review of the literature

Abstract: BackgroundIncidences of immune thrombocytopenic purpura occur in 1 in every 1000–10,000 pregnancies accounting for 3% of all thrombocytopenic pregnancies. A pre-existing immune thrombocytopenic purpura is known to be a risk factor for developing thrombocytopenia during pregnancy. We present here the treatment regime and management of a patient with known immune thrombocytopenic purpura who developed postpartum thrombotic thrombocytopenia with atypical response to traditional therapy.Pregnant women are more vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…In addition, preexisting ITP is a known risk factor for developing TTP during pregnancy. 14 Our patient had recurrent thrombocytopenia, and her ADAMTS13 level met the diagnostic criteria for TTP. However, the TTP subtype (congenital vs acquired) remains unknown since anti-ADAMTS13 IgG levels and genetic analysis were not performed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, preexisting ITP is a known risk factor for developing TTP during pregnancy. 14 Our patient had recurrent thrombocytopenia, and her ADAMTS13 level met the diagnostic criteria for TTP. However, the TTP subtype (congenital vs acquired) remains unknown since anti-ADAMTS13 IgG levels and genetic analysis were not performed.…”
Section: Discussionmentioning
confidence: 60%
“…Extremely low platelet levels, as seen in this patient, are known to cause intramyocardial hemorrhage, 16 and myocardial ischemia due to platelet thrombi was contributory to this death. Also, pregnancy is clearly a trigger for the development of ITP and TTP, 12,14,15,17 warranting a high index of suspicion in pregnant patients who develop thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports describing TTP complicated by AIH or ITP (3,4). It remains unclear whether there are differences in the clinical courses and outcomes between TTP patients with or without other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 This condition may be asymptomatic, diagnosed from routine laboratory tests, or may manifest more rarely as severe cases with petechiae, hemorrhages and hematomas. 7 Treatment is indicated for platelet counts below 30 Â 10 9 /L, with steroids and IgG as first line treatment, 8,9 and alternatively, thrombopoietin receptors agonists, 10 rituximab, 11 or, eventually, splenectomy (occasionally performed and, if necessary, in the 2 nd trimester of gestation). 12 Since there is no treatment with guaranteed effectiveness, many studies have shown that the clinical management of pregnancy, delivery, and puerperium in patients with thrombocytopenia needs a close cooperation of experienced hematologists, obstetricians, anesthesiologists and neonatologist.…”
Section: Discussionmentioning
confidence: 99%